1988
DOI: 10.1002/ajmg.1320290420
|View full text |Cite
|
Sign up to set email alerts
|

Variant of atelosteogenesis? Report of a 20‐week fetus

Abstract: We report on a 20-week fetus with manifestations similar, but not identical, to those of atelosteogenesis. The present fetus had rhizomelic micromelia with absence of ossification in the humerus, radius, ulna, and cervical and upper thoracic vertebral bodies; coronal clefts in the ossified thoracic vertebral bodies; and talipes equinovarus. The physes were relatively normal on histologic examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
6
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
5
6
0
Order By: Relevance
“…Although micromelia is easily recognizable by ultrasound, a specific diagnosis of A 0 has not been made prenatally. Sonographic evidence of severe bone shortening in cases subsequently diagnosed as A 0 by postmortem radiographic studies has been reported (Chevernak et al, 1986;Temple e f al., 1990;Sillence et al, 1987;Herzberg et al, 1988). The correlation of prenatal sonographic findings with post-mortem radiological studies demonstrated for the first time in this report establishes the feasibility of diagnosing antenatally many of the typical features of A 0 type 11.…”
Section: Discussionsupporting
confidence: 68%
“…Although micromelia is easily recognizable by ultrasound, a specific diagnosis of A 0 has not been made prenatally. Sonographic evidence of severe bone shortening in cases subsequently diagnosed as A 0 by postmortem radiographic studies has been reported (Chevernak et al, 1986;Temple e f al., 1990;Sillence et al, 1987;Herzberg et al, 1988). The correlation of prenatal sonographic findings with post-mortem radiological studies demonstrated for the first time in this report establishes the feasibility of diagnosing antenatally many of the typical features of A 0 type 11.…”
Section: Discussionsupporting
confidence: 68%
“…Not all the padents of Maroteaux et al (1982) were reported in complete detail, and it has been found that the changes in bone histopathology are variable in their extent and distribution, and may not be seen in all sections (Sillence et al 1982, our patient). Henberg et al (1988) did not find any abnormal bone histopathology in their case, and this, together with the relative severity of the skeletal findings, led them to question the possibility of a variant form of AT-I. An alternative explanation is that the pathologic changes represent a secondary phenomenon that is not present at 20 weeks of gestation, or were a function of the tissue sampled.…”
Section: Discussionmentioning
confidence: 92%
“…There was virtual absence of calcification of the vertebral bodies, the "radius" was the only forearm remnant, and unlike any previous report, the tibiae and femurs were not ossified. The radius and ulna in AT-I are often normal, or show relatively mild hypoplasia, although the 20-week fetus reported by Henberg et al (1988) had absence of the radii and ulnae. The digital changes were also marked.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The descriptions of patients with atelosteogenesis demonstrate considerable variability in the bones involved and the severity of the ossification defect [1,2]. A report in a 20-week fetus demonstrated more severe delay in vertebral ossification than in previously reported cases, and this fetus also lacked the tapering humeri or femora which are typical of atelosteogenesis [3].…”
Section: Discussionmentioning
confidence: 96%